2016
DOI: 10.4314/ajtcam.v13i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Physio-chemical evaluation and biological activity of <i>Ajuga bracteosa</i> wall and <i>Viola odoroto</i> Linn

Abstract: Background: Ajuga bracteosa and Viola odorata are frequently used by the native people of Swat-Pakistan for the curing of fever, malaria, cough, urinary and stomach disorders with slightly different practice of usage like raw powdered, extracts, decoction etc. Methods and Materials: Disc Diffusion Method was used for determination of antimicrobial activities of both plants. Nutrient Agar Media was used for the culturing and growth of all microbial strains. Vitamin C and minerals contents were determined by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…These results agree with Dalleau et al (2008), Pemmaraju et al (2013) and Zore et al (2011), who revealed that terpenoids isolated from subject plant showed excellent activity against Candida spp. These results were also similar to Shad et al (2016) …”
Section: Antifungal Activitysupporting
confidence: 80%
See 1 more Smart Citation
“…These results agree with Dalleau et al (2008), Pemmaraju et al (2013) and Zore et al (2011), who revealed that terpenoids isolated from subject plant showed excellent activity against Candida spp. These results were also similar to Shad et al (2016) …”
Section: Antifungal Activitysupporting
confidence: 80%
“…Bakht et al (2011), Kaithwas and Majumdar (2010), (2011) and Panda (2014) reported notable antibacterial activity of different fraction of L. usitatissimum which are in line with the present findings. The results also find supportive evidence from the study of Shad et al (2016) who observed that the methanol extract of the said plant showed appreciable bactericidal activity against S. aureus, B. subtilis, P. aeruginosa, and E. coli, respectively.…”
Section: Antibacterial Activitysupporting
confidence: 70%
“…Distinctive biodiversity of Pakistan includes more than 600 medicinal plants and people use these plants for medication purposes against fever, cough, and cold and to heal wounds. Ajuga bracteosa is native to Himalayan region, Afghanistan, China and Malaysia [5]. A. bracteosa being a promising herb has greater significance in rural areas of Pakistan and Azad Kashmir.…”
Section: Introductionmentioning
confidence: 99%